Similarity and Potential Relation Between Periimplantitis and Rheumatoid Arthritis on Transcriptomic Level: Results of a Bioinformatics Study - Li, Shiyi; Zhou, Changqing; Xu, Yongqian; Wang, Yujia; Li, Lijiao; Pelekos, George; Ziebolz, Dirk; Schmalz, Gerhard; Qin, Zeman (Frontiers in Immunology, 2021)
Background: This bioinformatics study aimed to reveal potential cross-talk genes, related pathways and transcription factors between periimplantitis and rheumatoid arthritis (RA). Methods: The datasets GSE33774 (7 periimplantitis and 8 control samples) and GSE106090 (6 periimplantitis and 6 control samples) were included from the NCBI Gene Expression Omnibus (GEO). A differential expression analysis (p<0.05 and |logFC (fold change) | >= 1) and functional enrichment analysis (p<0.05) were performed. Based on this, a protein-protein-interaction (PPI) network was constructed by Cytoscape. RA related genes were extracted from DisGeNET database and an overlap between periimplantitis related genes and these RA related genes was examined to identify potential cross-talk genes. Gene expression was merged between two datasets and feature selection was performed by Recursive Feature Elimination (RFE) algorithm. For the feature selected cross-talk genes, Support vector machine (SVM) models were constructed. The expression of these feature genes was determined from GSE93272 for RA. Finally, a network including cross-talk genes, related pathways and transcription factors was constructed. Results: Periimplantitis datasets included 138 common deregulated genes (DEGs) including 101 up- and 37 down-regulated DEGs. The PPI interwork of periimplantitis comprised of 1818 nodes and 2517 edges. The RFE method selected six features, i.e. MERTK, CD14, MAPT, CCR1, C3AR1, FCGR2B, which had the highest prediction. Out of these feature genes, CD14 and FCGR2B were most highly expressed in periimplantitis and RA. The final activated pathway-gene network contained 181 nodes and 360 edges. NF-kappa B signaling pathway and osteoclast differentiation were identified as potentially relevant pathways. Conclusions: This current study revealed FCGR2B and CD14 as the most relevant potential cross-talk genes between RA and periimplantitis, what suggests a similarity between RA and periimplantitis and can serve as a theoretical basis for future research.